(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines the complex interplay among dietary metabolism, physical activity, and general health. It explores the intricate physiological mechanisms behind the metabolism of macronutrients (proteins, fats, and carbs) and micronutrients, looking at how regular exercise affects hormone regulation, metabolic pathways, and energy expenditure. The impact of exercise on glucose metabolism is examined in this study through a review of the research, with a focus on how exercise helps control blood sugar levels and avoid metabolic diseases like diabetes. It also looks into how exercise affects protein metabolism, with a particular emphasis on muscle protein synthesis and repair, as well as the significance of getting enough protein in the diet for people who exercise in different ways. It is examined how exercise affects lipid profiles and cardiovascular health in addition to helping with weight management and fat metabolism. The wider effects of exercise on immune system performance, nutrition storage, and bone health are also included in the paper. This document attempts to provide a thorough understanding of how physical activity affects food metabolism and, in turn, general health by summarizing the results of recent research.